The Influence of Loss Distribution on the Temperature Field of High-Speed Induction Motor - Xiwei Yu; Deyun Chen; Xuandong Wu; Mengmeng Ai (IEEE Access, 2024)
The operating temperature of the motor is directly influenced by motor loss, and there is a significant difference in the distribution of loss between high-speed motor and conventional speed motor, so it is extremely important to analyze the temperature field of high-speed motor. The manuscript takes a high-speed induction motor as an example for three-dimensional temperature field analysis, calculates the temperature field of the motor under various loss conditions, and obtains the characteristic relationship between different loss and winding temperature and rotor squirrel cage temperature. The rationality of the simulation model and the correctness of the analysis results are verified by comparing the motor’s full load operation test with the simulation results. Finally, the basic design ideas for high-speed motors are summarized.